The cut-off point for tympanic temperature as a heat strain index for evaluation of outdoor workers: a field study. Issue 2 (3rd April 2018) - Heidari, Hamidreza; Golbabaei, Farideh; Shamsipour, Aliakbar; Rahimi Forushani, Abbas; Gaeini, Abbasali
Abstract : Objectives . The aims of this study were (a) to assess the agreement coefficient between tympanic temperatures and the most popular and valid heat stress index, wet bulb globe temperature (WBGT), in outdoor environments; (b) to determine a cut-off point for tympanic temperature as a heat strain index for evaluation of outdoor workers. Methods . 1452 measurements of WBGT index and tympanic temperature were recorded for outdoor workers from nine different climatic regions. Consistency of the WBGT and tympanic temperature were tested. The cut-off point for tympanic temperature in outdoor environments regarding WBGT evaluation was suggested based on obtained sensitivity and specificity from a receiver operating characteristic curve. Results . The results showed that there were numerous situations in which WBGT exceeded the reference value, whilst the measured values of tympanic temperature rarely reached a permissible value for core temperature (38 °C). Therefore, appropriate consistency of results between the heat stress and strain indices was not achieved. Conclusion . The criterion of tympanic temperature equaling 37 °C was suggested as a cut-off point for tympanic temperature as a heat strain index for outdoor environment evaluation.